Monitoring circulating gammadelta T cells in cancer patients to optimize gammadelta T cell-based immunotherapy - Oberg, Hans-Heinrich; Kellner, Christian; Peipp, Matthias; Sebens, Susanne; Adam-Klages, Sabine; Gramatzki, Martin; Kabelitz, Dieter; Wesch, Daniela (Frontiers in Immunology, 2014)
The success of gammadelta (gd) T cell-based immunotherapy, where the cytotoxic activity of circulating gd T lymphocytes is activated by nitrogen-containing bisphosphonates (n-BP), or possibly by bispecific antibodies or the combination of both, requires a profound knowledge of patients´ gd T cells. A possible influence of radio- or chemotherapy on gd T cells as well as their reported exhaustion after repetitive treatment with n-BP or their lack of response to various cancers can be easily determined by the monitoring assays described in this perspective article. Monitoring the absolute cell numbers of circulating gd T cell subpopulations in small volumes of whole blood from cancer patients and determining gd T cell-cytotoxicity using the Real-Time Cell Analyzer can give a more comprehensive assessment of a personalized tumor treatment. Possible future directions such as the combined usage of n-BP or phosphorylated antigens together with bispecific antibodies that selectively target gd T cells to tumor associated antigens, will be discussed. Such strategies induce expansion and enhance gd T cell-cytotoxicity and might possibly avoid their exhaustion and overcome the immunosuppressive tumor microenvironment.